Viability of Pineapple Leaves as an Alternative Natural Fiber Geotextile - C. Celis, Oliver (Institut Teknologi Sepuluh Nopember, 2017)
The study focuses on the utilization of pineapple leaves fiber as a raw material for the production of geotextiles. The fiber yarns were weaved based on required size of sample issued by the Philippines Textile Research Institute (PTRI) of the Department of Science and Technology (DOST). The Zwick/Roell Tensile Strength Tester Z050 (CRE) with 50 KN full scale load was used with the Wide-Width Strip Method in order to get the average tensile strength of the specimens each for both pineapple and abaca geotextile samples. The resulting average tensile strength and average nominal thickness for pineapple leaves geo-textile, when compared to abaca geo-textile has higher tensile force for a thinner sample of pineapple leaf geo-textile.